2007
DOI: 10.1126/science.1139560
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Regions Orchestrate Suppression of Emotional Memories via a Two-Phase Process

Abstract: Whether memories can be suppressed has been a controversial issue in psychology and cognitive neuroscience for decades. We found evidence that emotional memories are suppressed via two time-differentiated neural mechanisms: (i) an initial suppression by the right inferior frontal gyrus over regions supporting sensory components of the memory representation (visual cortex, thalamus), followed by (ii) right medial frontal gyrus control over regions supporting multimodal and emotional components of the memory rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
544
13
7

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 418 publications
(625 citation statements)
references
References 33 publications
61
544
13
7
Order By: Relevance
“…Forty-three participants from three age groups (fi fteen 8-9 year olds, fourteen 11-12 year olds, and 14 young adults) were scanned as they performed the Think/No-Think task. Aggregating across all 43 participants showed robust engagement of right DLPFC and VLPFC during retrieval suppression, and a clear reduction in hippocampal activity during Suppress trials, consistent with the foregoing imaging studies by Anderson et al ( 2004 ) and Depue et al ( 2007 ) . Moreover, activity in DLPFC was functionally related to activity in the hippocampus during retrieval suppression, indicating an interaction between these regions that helps to implement the process of retrieval suppression.…”
Section: Development Of Retrieval Suppressionsupporting
confidence: 60%
See 4 more Smart Citations
“…Forty-three participants from three age groups (fi fteen 8-9 year olds, fourteen 11-12 year olds, and 14 young adults) were scanned as they performed the Think/No-Think task. Aggregating across all 43 participants showed robust engagement of right DLPFC and VLPFC during retrieval suppression, and a clear reduction in hippocampal activity during Suppress trials, consistent with the foregoing imaging studies by Anderson et al ( 2004 ) and Depue et al ( 2007 ) . Moreover, activity in DLPFC was functionally related to activity in the hippocampus during retrieval suppression, indicating an interaction between these regions that helps to implement the process of retrieval suppression.…”
Section: Development Of Retrieval Suppressionsupporting
confidence: 60%
“…A particularly nice illustration comes from the study by Depue et al ( 2007 ) discussed earlier, in which participants showed a 9% negative control effect in their ability to recall scenes in response to faces (Fig. 7 ).…”
Section: Generalizes To Emotional Memoriesmentioning
confidence: 99%
See 3 more Smart Citations